Identification of Pathogenic Bacterial Contamination of Salmonella sp. in Fishery Products Using SNI ISO 6579:2015 - Burhana, Nanda Azizah; Surfiyanti, Oktarina; Agustina, Eva; Faizah, Hanik (Universitas Teuku Umar, 2024)
Indonesia is the largest archipelagic and maritime country in the tropical region with quite large potential for exploiting marine resources, especially in the fisheries sector. Quite a large amount of fishery products are marketed through modern markets and traditional markets in the form of fresh or frozen fish. Poor sanitation and hygiene in the processing and marketing of fishery products often lead to the spread of harmful bacteria, including Salmonella sp. This research aimed to detect Salmonella sp. contamination on five samples of fishery products, namely milkfish, tuna, catfish, shrimp and frog legs using the SNI ISO 6579:2015 method. The results showed that initial enrichment and selective media isolation detected Salmonella sp. in some samples, but biochemical tests ultimately confirmed that all samples were negative. This outcome complies with SNI ISO 6579:2015, which requires that food, including fish, must not contain Salmonella sp.